بنیاتی شێواز له‌ شیعری ڕۆژهه‌ڵاتی كوردستان - به‌ نموونه‌ی شیعری (چاوه‌) - خدر, پ.د. عوسمان حه‌مه‌د; محمود, شوان محمدأمین (Sulaimani Journal for Humanities, 2023)
The purpose of building the style of poetry in this research is to investigate the levels of the new language of poetry in the east of Kurdistan – for example, the poetry of "Chawa", because the levels of language are (phonetic, syntax, phonology, and semantics) play an important role in building literary texts, so it has been given special importance in investigating new criticisms, because The researcher can recognize the style of writers through time and separate their products Because of the importance of this issue and the lack of any research in this way, especially on the products of Chawa in this research, which has been tried in the first part in a theoretical way and in the second part practically talked about language and style and Build new poetry in this part of Kurdistan.
Keywords: New Poetry language; style; levels of language